Neonatal expression of amh, sox9 and sf-1 mRNA in Caiman latirostris and effects of in ovo exposure to endocrine disrupting chemicals - Durando, Milena de Lourdes (2013)
Caiman latirostris is one of the reptilian species that exhibits temperature-dependent sex determination (TSD). In addition, male-to-female sex reversal after in ovo estrogen/xenoestrogen exposure was demonstrated, called as hormone-dependent sex determination (HSD). The amh, sox9 and sf-1 genes are involved in sex determination, sex differentiation, and steroidogenesis. The aims of this study were: a) to establish the expression patterns of amh, sox9 and sf-1 mRNA in the gonad-adrenal-mesonephros (GAM) complexes of neonatal TSD-male and TSD-female caimans, b) to compare the expression of these genes between TSD-females versus HSD-females (born from E2-exposed eggs incubated at the male-producing temperature) and c) to evaluate whether these genes are affected by in ovo exposure to 17b-estradiol (E2) and two endocrine disrupting chemicals (bisphenol A (BPA) or endosulfan (END)). The mRNA expression of amh, sox9 and sf-1 in GAM complexes from TSD-males and TSD-females, and from HSD-females were quantitatively compared by RT-PCR. In neonatal caimans, we demonstrated a sexually dimorphic pattern of amh and sox9 mRNA expression, with a higher expression in TSD-male than in TSD-female GAM. sf-1 mRNA did not differ between TSD-males and TSD-females. Between females, HSD-females exhibited a higher expression of sox9 than TSD-females. Increased mRNA expression of sex-determining genes was observed in the GAM of neonatal males, in ovo exposed to END. No changes were observed after BPA exposure, and E2 decreased the sox9 but increased the sf-1 mRNA expression. These results provide a new insight into the mechanisms of gonadal histo-functional alterations in caimans exposed to contaminated environments.